Economic Efficiency in Edgeworth Box Market the Case of Two Goods - DEDA, Eriona; SULI, Dudi; SULI, Hergys (European Journal of Sustainable Development, 2013)
Is very important for our markets, anappreciation for some of benefits oftrade and understanding to how pricesget established in simple markets.The Edgewrth box serves to orient themarkets scientifically and at the sametime can be used by decision makers inthe planning resources process tomeet customer demand. Using a production Edgewrth box , shows thatefficiency in production has similar properties to efficiency in distribution.From the optimal choices inside theEdgeworth box, we derive a productionpossibilities frontier that describes allthe efficient combinations of twogoods to maximize the benefit of both consumers. The Edgewrth box servesto orient the markets scientifically and at the same time can be used bydecision makers in the planning resources process to meet customer demand.To analyze efficiency in production weuse Edgeworth box. In the Edgeworthbox, we analyze how the market achieves a competitive equilibrium.